Adolescent Coordinated Transition (ACT) to improve health outcomes among young people living with HIV in Nigeria: study protocol for a randomized controlled trial - Sam-Agudu, Nadia A. (Trials, 2017)
BACKGROUND: Adolescents living with HIV (ALHIV) have worse health outcomes than other populations of people living with HIV. Contributing factors include lack of standard and comprehensive procedures for ALHIV transitioning from pediatric to adult care. This has contributed to poor retention at, and following transition, which is problematic especially in high ALHIV-burden, resource-limited settings like Nigeria. METHODS: Using a two-arm cluster randomized control design, the Adolescent Coordinated Transition (ACT) trial will measure the comparative effectiveness of a graduated transition and organized support group intervention against the usual practice of abrupt transfer of Nigerian ALHIV from pediatric to adult care. This study will be conducted at 12 secondary and tertiary healthcare facilities (six intervention, six control) across all six of Nigeria’s geopolitical zones. The study population is 13- to 17-year-old ALHIV (N = 216, n = 108 per study arm) on antiretroviral therapy. Study participants will be followed through a 12-month pre-transfer/transition period and for an additional 24 months post transfer/transition. The primary outcome measure is the proportion of ALHIV retained in care at 12 and 24 months post transfer. Secondary outcome measures are proportions of ALHIV achieving viral suppression and demonstrating increased psychosocial wellbeing and self-efficacy measured by psychometric tests including health locus of control, functional social support, perceived mental health, and sexual risk and behavior. DISCUSSION: We hypothesize that the ACT intervention will significantly increase psychosocial wellbeing, retention in care and ultimately viral suppression among ALHIV. ACT’s findings have the potential to facilitate the development of standard guidelines for transitioning ALHIV and improving health outcomes in this population. The engagement of a consortium of local implementing partners under the Nigeria Implementation Science Alliance allows for nationwide study implementation and expedient results dissemination to program managers and policy-makers. Ultimately, ACT may also provide evidence to inform transitioning guidelines not only for ALHIV but for adolescents living with other chronic diseases in resource-limited settings. TRIAL REGISTRATION: ClinicalTrials.gov, ID: NCT03152006. Registered on May 12, 2017. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13063-017-2347-z) contains supplementary material, which is available to authorized users.